MENANGKAP PESAN-PESAN HUKUM DALAM ALQURAN (Alternatif dan Solutif Penggunaan Metode Tafsir Kontekstual Dalam Menghadapi Kasus-Kasus Kontemporer) - Arsal Arsal (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2016)
The process of decline in the Qur'an was over a few centuries ago, and now that there is in the form of texts. As a last book, he serves as instructions and guidelines to organize human life and he did not know the limits of space and time in spite of the decline in local- temporal, but its message is universal and timeless. As a text, the Koran is an open corpus is of course an opportunity to reread, reinterpreted, and understood its content with relevant methods and thus Quran can mersepon and answered development of human life. Without degrading methods of interpretation set by previous scholars, presumably the method needs to be enriched with new methods. Contextual interpretation method is considered a new method, an alternative understanding the content of the Qur'an is right to address problems of contemporary and contemporary.